Sosialisasi Pemanfaatan Limbah Botol PET menjadi Ecobrick di SD Inpres Kantisang-Tamalanrea - Mary Selintung; Asiyanthi Tabran Lando; Muralia Hustim; Kartika Sari; Rasdiana Zakaria; Nur An-nisa Putry Mangarengi; Abdul Nasser Arifin (Faculty of Engineering UNHAS, 2021)
Plastics are widely used in various kinds of human life needs. The most important problem is plastic waste which cannot be decomposed naturally. It takes a very long time to clean plastic waste from the face of the earth. Moreover, the use of plastic is almost uncontrollable. Ecobrick is a creative effort to manage plastic waste into useful objects, reducing pollution and toxins generated by plastic waste. Its function is not to destroy plastic waste, but to extend the life of these plastics and process them into something useful, which can be used for the benefit of humans in general. Ecobricking is a plastic waste management technique made from used plastic bottles in which various plastic waste has been filled to the brim and then compacted until it becomes hard. After the bottles are full and hard, they can be assembled with glue and assembled into tables, simple chairs, building materials for walls, towers, small stages, and even have the potential to be assembled into fences and foundations for simple playgrounds and even houses. The partners involved in this Community Service activity are students and teachers at SD Inpres Kantisang. The solution offered is the management and processing of PET bottle waste that arises from the school environment into ecobricks which can be reused in the school environment. Due to the COVID-19 pandemic, the socialization carried out is by providing flash media to the school. The flashdisk contains educational and animated videos, as well as instructions for sorting waste and making ecobricks. The school will include this socialization material in Thematic learning in grade 5 and grade 6, and it is also used as a support for the Adiwiyata program at SD Inpres Kantisang - Tamalanrea.